PEST ANALYSIS IN THE SYSTEM OF MARKETING ANALYSIS OF AGRICULTURAL ENTERPRISES - GUDZ, Iurii; KARPENKO, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The transition of the agrarian sphere of the economy to market relations requires the formation of a new adequate market of the economic mechanism of management. Its most important element is marketing, in which the main role of the production and marketing activities of agro-industrial complex enterprises, regardless of the forms of ownership, is determined by the consumer. Practice shows that the complexity of the problems of exiting the crisis is determined not only by the lack of management experience in new conditions, but also by the weak validity of the conceptual support of transformations in the agrarian sphere. There are still no worked-out approaches to the creation and development of federal and regional agricultural marketing systems, methodical developments for the rational planning of marketing activities in the agro-industrial complex enterprises themselves, methods for evaluating the economic effectiveness of marketing strategies being implemented, etc. The most productive way of obtaining information in the developing market environment is marketing research, which is a multidimensional process of analyzing the internal and external environment of business entities, aimed at the development of adequate management decisions and ensures the minimization of various threats and risks. In the conditions of socio-economic reform of the agro-industrial sphere, information turns into a leading production factor, and the activity of its collection, transmission, storage, processing and analysis becomes one of the most important management technologies. The fate of a new product, and sometimes the fate of the enterprise itself, depends on the completeness, objectivity, reliability, systematicity, timeliness and periodicity of information. PEST analysis is a simple and convenient method for analyzing the macro environment (external environment) of the enterprise. The PEST analysis technique is often used to assess key market trends in an industry, and the results of a PEST analysis can be used to identify a list of threats and opportunities when compiling a company's SWOT analysis. The PEST analysis is a long-term strategic planning tool and is prepared 3-5 years in advance, with annual data updates
Keywords: marketing; analysis; agricultural enterprise; factors; strategic planning; strategy